Mucopolysaccharidosis: MRI Study - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Characteristic changes in the MRI of 2 brothers with mucopolysaccharidosis type I are reported from the Departments of Paediatrics, Neuroradiology and Neurology, University of Ancona, Italy.